Effects of temperature and lead core heating on response of seismically isolated bridges under near-fault excitations. Issue 14 (October 2019) - Wang, Hao; Zheng, Wen-Zhi; Li, Jian; Gao, Yu-Qi
Seismic responses of bridges isolated by lead rubber bearings under near-fault excitations are presented in this article. A bilinear force-deformation model is employed to represent the hysteretic behaviors of lead rubber bearings. The joint effects of ambient temperature, initial displacement, and lead core heating on the responses of seismically isolated bridges are investigated. Nonlinear time history analyses are conducted with the employed hysteretic models of lead rubber bearings. Comparisons of the responses with and without the joint effects are performed, in terms of maximum isolator displacements, maximum isolator forces, and base forces of the piers. Results show that ambient temperature, initial displacement, and lead core heating have significant joint effects on the responses of seismically isolated bridges. When such joint effects are ignored at low temperatures, the maximum isolator displacements could be overestimated, whereas the maximum isolator forces and the base forces could be underestimated. However, as for ambient temperatures above 20°C, the maximum isolator displacements could be underestimated, whereas the maximum isolator forces and the base forces could be overestimated with small maximum isolator displacements and underestimated with large maximum isolator displacements.